De juegos y de territorios. Comprensiones otras del ocio en sociedades de la periferia (2012)
ABSTRACT: This paper has been placed in a purpose for the decolonization of practices, manifestations and social meetings, which have been hidden by dominant speech. A speech that grants privileges to certain categories, and ways to name what people and community think and do in their everyday life. It deals with vindicating of another logical ways of thought and experience which give sense to the life some human being groups. According to Silvia Rivera Cusicanqui, author and Bolivian activist, they seek the recovery of categories which are determinant and own to indigenous communities to describe and tell their lives. It is, if preferred, and awakening, but not of Modernity, but of the recovery of the Voice, the word from communities which have been silenced and subordinated for a long time.